Study-work-life balance of international students in the context of temporal boundaries - O'Mahony , Megan; Jeske , Debora (Journal of Interdisciplinary Studies in Education, 2019)
The goal of this qualitative study was to examine the experience of study-work-life balance among international students who were separated from their family both geographically and temporally. Using 10 semi-structured interviews with postgraduate students and thematic analysis, several themes were identified. These included boundary management shifts due to study/work demands and time zone differences. In addition, students reported social and personal challenges (in terms of family’s expectations, relationships maintenance, socialization in host country). Temporal boundaries contributed to social withdrawal and isolation among students, many of which were heavily reliant on their own family network for support. The findings strengthen the argument that time difference impacts the boundary management and social experience of international students.